Effect Of Solution Annealing On Microstructure, Corrosion And Mechanical Property Of Sensitized AISI 316 - Mahzan, Johar (UTeM, 2010)
AISI 316 is stainless steels that commonly used in industries. AISI 316 is the most favored construction material of various components required in chemical, petrochemical and nuclear industries. It is important to study the corrosion properties of AISI 316 due to the mechanical properties, microstructure and corrosion attack. Two types of corrosion attack that commonly found on AISI 316 stainless steels are intergranular corrosion and pitting corrosion. Intergranular corrosion is occurring when AISI 316 is sensitized to the heat at temperature 500ºC to 800°C leads to the grain boundary precipitation of chromium rich carbides (Fe,Cr)23C6 and the formation of chromium depletion regions (Uhlig, H. H. 2008). The process of solution annealing followed by rapid quenching can cure the intergranular corrosion in AISI 316. Pitting corrosion occurs due to the attack of the corrosive environment to the heterogeneous material composition on the surface of the AISI 316 where at the surface region, black spot that contain high iron will ease attack by localize corrosion and form pitting. The formation of respective corrosion is studied by using electrochemical analysis and the oxalic etch test for classification of etch structures in determining the suitability of intergranular corrosion. Potentiodynamic Cyclic Polarization as described in ASTM standard G 61 is applied in order to analyze the formation of pitting and the behavior of AISI 316 in resisting corrosion. In this study, intergranular corrosion is investigated by exposing AISI 316 at sensitized temperature. Based on the experiment, it shows that after AISI 316 exposed to sensitized temperature, AISI 316 is susceptible to intergranular corrosion attacked. Solution annealing had been used in order to improve corrosion behavior of AISI 316 for resisting intergranular corrosion. The corrosion product that had been propagates on surface of AISI 316 was analyzed by Optical Microscope (OM). X-Ray Diffraction (XRD) Analysis applied to analyze the phase of chromium carbide form in the structure of AISI 316. This formation had been analyzed that this phases cause